Production characters of the Sahiwal and Ayrshire breeds and their crosses in Kenya - Trail, J.C.M.; Gregory, K.E. (Springer, 1982)
Presents comparative data on reproductive and productive performances of cows of pure Ayrshire and Sahiwal breeds or their reciprocal crosses and their progeny w. Ayrshire, Sahiwal, Simmental and mixed breed bulls in the lower to mid-potential temperate highland zone of Kenya; with particular reference to age at first calving, calving interval, milk yield, lactation and dry period length for cows; birth and weaning weights of calves; post weaning growth of heifers; and mortality of calves and cows. Analyses effects of year and month of birth, breeding group and breed of sire on above parameters and includes a cow-productivity index for each breed.